A novel SMA-magnetorheological hybrid bracing system for seismic control. (1st October 2021) - Zareie, Shahin; Issa, Anas Salem; Seethaler, Rudolf; Zabihollah, Abolghassem; Ahmad, Rafiq
Highlights: SMA-based cable is suggested to use for the tension leg platform. The long-term periodical loading is simulated by applying cyclic loading on the SMA specimen. Effect of cyclic loadings 0% and 1.7% pre-strained SMA-wire is investigated. The changes in the superelasticity and energy dissipation capacity of 0% pre-strained SMA-wire are observed. The safety factor is proposed to use for SMA-based cables. Abstract: Maintaining the stability of civil structures under excessive dynamic loads, including earthquakes and windstorms, has always been a big challenge for researchers and designers in structural engineering communities. The recent integration of multi-functional smart materials into structural bracing systems has opened a new horizon in civil engineering to control and maintain the structural stability of civil infrastructures. A hybrid smart bracing system based on Magnetorheological Fluid (MRF) and Shape Memory Alloy (SMA) has been developed in the present study. To examine the performance and functionality of the developed model, numerical simulations are conducted under quasi-static load conditions. Compared to the individual SMA-based bracing and MRF-based bracing systems, the proposed hybrid system considers both active and inactive modes of the MRF-based system to illustrate its superiority and highlight its advantages. Additionally, the effect of the two most common SMA materials on the dynamic behavior of the bracing has been studied. The results show significant improvements in the energy dissipation capacity and the re-centering ability of the hybrid bracing system.